Karakteristik Mutu dan Sensori Nugget Ikan Patin (Pangasius hypopthalmus) dan Nangka (Artocarpus heterophyllus) Muda - Dewi Fortuna Ayu; Diana Sari Sormin; Rahmayuni Rahmayuni (Jurnal Teknologi dan Industri Pertanian Indonesia, 2020)
The purpose of this research was to study the effect of catfish and young jackfruit ratio on quality and sensory nuggets.  A completely randomized design with four treatments and four replications was conducted in the research.  The treatments were PN1 (70 catfish meat: 30 young jackfruits), PN2 (60 catfish meat: 40 young jackfruits), PN3 (50 catfish meat: 50 young jackfruits), and PN4 (40 catfish meat: 60 young jackfruits).  Data obtained were statistically analyzed using analysis of variance and continued with Duncan's New Multiple Range Test (DNMRT) at a 5% level.  The results showed that the combination ratio of catfish and young jackfruit significantly affected water, ash, fat, protein, and crude fiber content, as well as descriptive sensory assessments such as color, aroma, taste, texture, and hedonic assessment of the nugget.  The best treatment was PN1 (70 catfish meat: 30 young jackfruit) which had fulfilled quality requirements of fish nuggets (SNI 7758-2013) i.e. 58.36% moisture content with a maximum value of 60%, 1.81% ash content with a maximum value of 2,5%, 4.94% fat content with a maximum value of 15%, 14.38% protein content with a minimum value of 5%, and 5.14% crude fiber content.  The overall sensory assessment of the nugget was a yellow color, flavorful of patins fish aroma, the very taste of patin fish (according to typical raw materials), and rather hard texture.